Benefits from optimised antihypertensive and statin treatment in high risk people. (14th October 2021) - Wu, R; Rison, S; Raisi-Estabragh, Z; Dostal, I; Carvalho, C; Robson, J; Mihaylova, B
Abstract: Background: Hypertension and hypercholesterolaemia are major modifiable risk factors for cardiovascular diseases (CVD) with available effective and low-cost treatments. However, their suboptimal treatment remains widespread. We characterise treatment gaps in a large urban population and quantify the potential long-term health and economic impact with optimised use. Methods: We studied 1 million UK urban residents served by 123 primary care practices in 2019. We categorised antihypertensive treatment in adults with diagnosed hypertension, and statin treatment in adults with diagnosed CVD, into optimal, suboptimal and not treated following UK clinical guidelines. A long-term CVD model was used to project cardiovascular events avoided, years of life and quality-adjusted life years (QALYs) gained, and healthcare costs saved with optimised treatments for individual patients accounting for their socio-demographic characteristics and risk factors. Results: 21, 954 (24%, mean age 59 years; 49% female) of the 91, 828 adults with hypertension were either suboptimally treated (20%) or untreated (4%) and 9, 062 (38%, mean age 69 years; 43% female) of the 23, 723 adults with CVD were either suboptimally treated (24%) or untreated (14%). Per 1000 patients (95% CI) optimised over lifespan, hypertension treatment would prevent 154 (72–230) major vascular events (MVEs, including heart attack, stroke or arterial revascularisation) and 69 (28–103) vascular deaths, and gain 769 (436–1038) QALYs for those sub-optimally treated, and prevent 138 (68–201) MVEs and 50 (21–76) vascular deaths, and gain 674 (386–920) QALYs for those not treated; statin treatment would prevent 68 (46–88) MVEs and 17 (12–21) vascular deaths, and gain 145 (113–178) QALYs for those sub-optimally treated, and prevent 260 (190–319) MVEs and 55 (40–68) vascular deaths, and gain 535 (412–651) QALYs for those not treated (Figure). Hospital cost savings net of medication costs were about £1100 per person over their remaining lifespan. Conclusion: Optimising preventive cardiovascular treatments in UK primary care is likely to cost-effectively reduce cardiovascular risk and improve life expectancy, while reducing population inequalities. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Barts Charity, British Heart Foundation, and Health Data Research UK